Electrically evoked mismatch negativity from speech stimuli as an objective measure of cochlear implant performance - Lichun Zhang; Pattric Stauga; David Mißler; Karsten Ehrt; Wilma Großmann; Robert Mlynski; Florian Herrmann Schmidt (Frontiers in Neuroscience)
IntroductionCochlear implant (CI) success is often assessed using subjective tests like word recognition scores (WRS). However, these tests are unsuitable for children, non-native speakers, and individuals with cognitive impairments. Mismatch negativity (MMN), an objective measure of cortical auditory processing, offers a promising alternative for evaluating speech perception. This study aimed to assess speech perception in CI patients using MMN and examine its correlation with WRS.MethodsThe study included 23 ears from CI users fitted for at least six months. Speech stimuli were presented via direct audio input to the CI processor at 70 dB nHL using an MMN paradigm. The syllables ‘ba’ (standard) and ‘da’ (deviant) served as stimuli. MMN amplitude and latency were analyzed, and their correlation with WRS was examined.ResultsA significant correlation was observed between WRS and MMN responses. CI users with lower WRS scores exhibited reduced MMN amplitudes and prolonged latencies compared to those with higher scores, indicating impaired cortical speech processing.DiscussionThese findings suggest that speech-induced MMN could serve as an objective tool for assessing speech perception in CI users. MMN provides valuable insights for optimizing CI fitting, particularly for patients unable to undergo subjective testing. Integrating MMN into clinical practice could improve speech perception outcomes and enhance the quality of life for CI users.